A preliminary study of water quality index in Terengganu River Basin, Malaysia - Suratman, S.; Mohd Sailan, M.I.; Hee, Y.Y.; Bedurus, E.A.; Latif, M.T. (Universiti Kebangsaan Malaysia, 2015)
The Malaysian Department of Environment-Water Quality Index (DOE-WQI) was determined for the Terengganu River basin which is located at the coastal water of the southern South China Sea between July and October 2008. Monthly samplings were carried out at ten sampling stations within the basin. Six parameters listed in DOE-WQI were measured based on standard methods: pH, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS) and ammonical nitrogen (AN). The results indicated the impact of various anthropogenic activities which contribute to high values of BOD, COD, TSS and AN at middle and downstream stations, as compared with the upstream of the basin. The reverses were true for the pH and DO values. The DOE-WQI ranged from 71.5-94.6% (mean 86.9%), which corresponded to a classification status range from slightly polluted to clean. With respect to the Malaysia National Water Quality Standards (NWQS), the level of most of the parameters measured remained at Class I which is suitable for the sustainable conservation of the natural environment, for water supply without treatment and as well as for very sensitive aquatic species. It is suggested that monitoring should be carried out continuously for proper management of this river basin.